Representation of Working Class in Alan Sillitoes Fiction: Exploring the portrayal of the working class in Alan Sillitoe's fiction (Journal of Advances and Scholarly Researches in Allied Education, 2018)
From a comprehensive perspective, fiction is any abstract story, which is concocted. For instance, Jonathan Swift's Gulliver's Travels. In a smaller sense, fiction is any scholarly account, ordinarily in writing (that incorporates short story) which might be true to life, authentic or nonfictional. Fiction implies novel, nonetheless. The 'common fiction' alludes to a sort of verifiable or contemporary reality. It is a sort of truth. This collection of fiction that is mostly previous history (as on account of its portrayal in Dickens' Hard Times) and part of the way contemporary reality (as on account of Alan Sillitoe's exemplary novel Saturday Night and Sunday Evening (1958), utilizes impersonation, creative mind and fictiondevelopment. It is imaginary portrayal of some kind of common talk. It addresses the common individuals' verbal activity, revealing, depicting and alluding.